2021
DOI: 10.3390/pathogens10020189
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Capridine β as a Consequence of Its Biotransformation into Metabolite Affecting Yeast Topoisomerase II Activity

Abstract: In the last few years, increasing importance is attached to problems caused by fungal pathogens. Current methods of preventing fungal infections remain unsatisfactory. There are several antifungal compounds which are highly effective in some cases, however, they have limitations in usage: Nephrotoxicity and other adverse effects. In addition, the frequent use of available fungistatic drugs promotes drug resistance. Therefore, there is an urgent need for the development of a novel antifungal drug with a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…As previously reported, C-1305 diminished the relaxation reaction by 50% at a concentration of 2.5 μM and totally inhibited human topoisomerase II-mediated relaxation at 10 μM [31] The same level of hTOPO II inhibition ability was determined for C-1311 (IC50 2.5 μg mL −1 6.5 μM) [14]. The previously reported modest inhibitory effect of m-AMSA on yTOPO II [15] indicates that the fungal enzyme might be sufficiently distinct from its human counterpart Our results concerning yeast DNA topoisomerase II inhibition measured by relaxation for C-1311 and C-1305 also suggest differences in sensitivity to the presence of both compounds. Although the human enzyme seemed to be more sensitive than the yeast one, it is likely to find antifungal compounds that are inactive against the former but inhibit the latter.…”
Section: Inhibition Of the Relaxation Activity Of Yeast Topoisomerase...supporting
confidence: 79%
See 3 more Smart Citations
“…As previously reported, C-1305 diminished the relaxation reaction by 50% at a concentration of 2.5 μM and totally inhibited human topoisomerase II-mediated relaxation at 10 μM [31] The same level of hTOPO II inhibition ability was determined for C-1311 (IC50 2.5 μg mL −1 6.5 μM) [14]. The previously reported modest inhibitory effect of m-AMSA on yTOPO II [15] indicates that the fungal enzyme might be sufficiently distinct from its human counterpart Our results concerning yeast DNA topoisomerase II inhibition measured by relaxation for C-1311 and C-1305 also suggest differences in sensitivity to the presence of both compounds. Although the human enzyme seemed to be more sensitive than the yeast one, it is likely to find antifungal compounds that are inactive against the former but inhibit the latter.…”
Section: Inhibition Of the Relaxation Activity Of Yeast Topoisomerase...supporting
confidence: 79%
“…Thus, one may conclude that the efficient accumulation of Compound 1-R8 resulted in fungal cell death in contrast to Compound 1 or R8. However, as indicated in Figure 5, there is a greater proportion of cells with an accumulated conjugate than PI-positive cells after 1 h and 3 h. The most effective Compound 1 totally inhibited the yeast topoisomerase II-mediated relaxation (Figure 6) at a concentration of 50 µM, lower than that detected for m-AMSA (IC 50 > 200 µM) [15]. m-AMSA, an acridine derivative, was the first synthetic drug approved for clinical usage that was shown to act as a human topoisomerase II (hTOPO II) inhibitor [17].…”
Section: Inhibition Of the Relaxation Activity Of Yeast Topoisomerase...mentioning
confidence: 85%
See 2 more Smart Citations
“…The antifungal activity of flavonoids against Candida species is shown through various mechanisms, including inhibition of fungal cell wall synthesis, disruption of fungal cell membrane integrity, and interference with fungal cell signaling pathways. Various flavonoids have been extracted and investigated for their antifungal activity, suggesting that they may have potential as efficient and costeffective therapies for candidiasis [1,5,15]. Hussain et al has shown the potency of quercetin, catechine, and hydroxybenzyltaxifolin isolated from mango (Mangifera indica L.) leaves in suppressing fungal growth [16].…”
Section: Introductionmentioning
confidence: 99%